EVALUATING THE EFFECTIVENESS OF AN IN-SERVICE SCIENCE PROGRAM THROUGH THE USE OF MATERIALS. - Stronck, David R.; Koller, Geraldine R. (Journal of Research in Science Teaching, 1981)
The article reports on the study that examines the effectiveness of an in-services science program through measuring the use of materials available from the school district's resource supply center in the U.S. The Science Curriculum Improvement Study was introduced by this inservice program into all 35 elementary schools of one district. The unobtrusive means of measuring teachers' behaviors is the live-material shipment orders. There is no difference between the 168 participants in the workshop before implementation and other 361 teachers in their use of materials.